Sedulur Sikep Indigenous Community Environment Balance During Covid-19 Pandemic - Utomo, St. Laksanto (CENTRAL ASIA AND THE CAUCASUS, 2024)
The environmental balance of the Sedulur Sikep customary law community during Corvid 19 pandemic remains consistent. They believe that the COVID-19 pandemic emerged as a natural reaction to what humans have done, as a sign that the earth has begun to judge. They stated that the COVID-19 outbreak confused all circles and made it difficult to get food. It was found that local wisdom regarding the environment of Sedulur Sikep implies the harmony of life with the North Kendeng Mountains. They implement the local wisdom in their daily life, including refusing the construction of the cement industry in North Kendeng Mountain. The reason for the refusal was based on the argument that the existence of the cement factory was damaging and disturbing the environmental balance on Mount Kendeng. The Sedulur Sikep Indigenous Community through the Community Care Network for the Kendeng Mountains (CCNKM) stated that the Kendeng ecosystem was threatened with the destruction of the Kendeng Mountains becoming more open. In the midst of the Covid 19 crisis, CCMKN reminded all parties to reduce the risk as small as possible due to the pandemic outbreak caused by human greed for nature. One example, in the midst of the current Covid 19 pandemic, in Rembang and Pati, Kendeng limestone mining continues. Large Scale Social Restriction (LSSR) which can actually stop exploitation in the Kendeng Mountains but is ignored.